Evaluating the colour stability of esthetic resin composite: A study of Neospectra ST under different staining conditions - Kondipudi, Nimisha; Likhitha Palla; Borugadda, Roopesh; Neelima, U Lavanya; Manchem, Aishwarya; Nawaz, Mohammad A K (International Journal of Dental Materials, 2024)
Background: There is a burgeoning interest in the colour permanence of aesthetic restorations, although only a handful of studies have been documented thus far. Aim: To investigate the impact of various common staining solutions on nanohybrid composite resin.. Materials and methods: Forty disk-shaped specimens (10 X 2 mm) were fabricated with Neo SpectraST composite material. The specimens were divided into four groups with 10 specimens (n=10) in each, based on the staining solutions, Group I: Turmeric, Group II: Coffee, Group III: Coke, and Group IV: Distilled water. Baseline measurements were taken using an ultraviolet spectrophotometer. Each sample group was immersed in their respective staining solutions, and the colour changes were recorded after 1, 7, and 14 days of immersion using the same spectrophotometer. The absorption values were recorded within the 300 to 800 nm range at baseline and after the immersion. The data was collected and subjected to statistical analysis. Results: Neo spectra ST composite showed the maximum staining capacity with the turmeric group compared to other staining solutions. One-way ANOVA showed significant differences (p=0.000) among the staining solutions at different time intervals. Repeated measures ANOVA displayed significant differences within the staining solutions (Turmeric: p=0.005; Coffee: p=0.001; and Coke: p=0.001) at different time intervals. Conclusion: The nanohybrid composite resin showed a significant colour change to turmeric compared to other staining solutions.